Combined effect of carrying both CFH (rs1061170) and TGFβ1 (rs1800469) gene variants on the risks of various forms of age-related macular degeneration - D.O. Peretiahina; N.A. Ulianova; L.Ie. Fishchuk; Z.I. Rossokha (Ukrainian Society of Ophthalmologists, 2023)
Background: Age-related macular degeneration (AMD) is one of the most common disorders that can lead to total central vision loss after choroidal neovascularization or geographic atrophy (GA). Because the genetic component of the disease plays an important role in the pathogenesis, has an impact on the clinical presentation, and determines the response to treatment, studies on the genetic component of AMD are relevant for better understanding the molecular mechanisms underlying the pathogenesis. Purpose: To investigate associations among TGFβ1 C509T (rs1800469) and CFH T1277С (rs1061170) polymorphisms, their gene-to-gene interactions and the risks of various forms of AMD. Material and Methods: This was a case-control study. The case group included 61 patients with AMD. Of these, 31 were diagnosed with late dry AMD (GA), and 30, with wet AMD (neovascular AMD or nAMD). Patients with nAMD were divided into two subgroups of 14 patients with type 1 or occult subretinal neovascular membrane (SNM), the SNM1 subgroup and 16 patients with type 2 or classical SNM, the SNM2 subgroup. The control group was composed of 50 individuals with no eye disease and of an age distribution similar to that of the case group. Polymerase chain reaction (PCR) and restriction analysis of gene amplification products were performed to determine TGFβ1 rs1800469 and CFH rs1061170. Results: We found a significant effect of TGFβ1 C509T (rs1800469) and CFH T1277C (rs1061170) gene variants on the risks of various forms of AMD. CFH 1277TT genotype was associated with decreased AMD risk, whereas 1277CC genotype, with increased AMD risk (first and foremost, increased GA risk) (р < 0.05). TGFβ1 509CC genotype was associated with increased risk, whereas TGFβ1 509TT genotype, with decreased risk of both GA and SNM2. Conclusion: For the first time, a combined effect of gene variants of interest on the susceptibility to the development of AMD has been investigated, and synergism between these variants in increasing the risk of certain forms of the disease (e.g., GA) established. The results obtained create prerequisites for developing individualized prediction of risk and novel treatment strategies for the disease.